Prototype Hybrid Power Plant of Solar Panel and Vertical Wind Turbine as a Provider of Alternative Electrical Energy at Kenjeran Beach Surabaya - Anggara Trisna Nugraha; Priyambodo , Dadang (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
Indonesia, which is a tropical country, has a very large potential for solar energy because of its area that stretches across the equator, with a radiation magnitude of 4.80 kWh / m2 / day or equivalent to 112,000 GWp. On the other hand, the earth receives solar power of 1.74 x 1017 W / hour and about 1-2% of it is converted into wind energy. However, from the total energy potential, Indonesia has only utilized around 10 MWp for solar energy and not much different, wind energy, whose utilization is planned to reach 250 MW in 2025, has only been utilized around 1 MW of the total existing potential. With this potential, to be able to supply additional power and help save energy for existing facilities in the building, a Prototype of Solar Panel Hybird and Vertical Axis Wind Turbine was created. The design of this prototype is a combination of savonious type turbines and solar panels, where the use of this type of turbine is because it can rotate at low wind speeds (low wind velocity) and its construction is very simple.